The Circulation of Palestrinian Polyphony in the South of Portugal during the Eighteenth Century: The Repertories of Évora, Elvas and Vila Viçosa - Henriques, Luís (2020)
Several books containing polyphonic works by Giovanni Pierluigi da Palestrina were copied during the first half of the eighteenth century for use in the churches of Évora and Elvas, and the chapel of the Ducal Palace in Vila Viçosa. This was probably a consequence following the desire of the Portuguese King D. João V and the import of the so-called “Roman monumental style” for the religious musical institutions of Lisbon, a model that markedly influenced the composition of sacred music in Portugal during the eighteenth century. Together with works in concertato style, the Roman style was largely based on the return to old practices such as the writing and performance of vocal polyphony in the Palestrinian style, imitating the musical practices of the Capella Giulia in Rome. Besides the churches of Lisbon, most of the other Portuguese musical religious institutions adopted this practice. In the case of Alentejo we find several choirbooks copied for the ducal chapel in Vila Viçosa and the cathedrals of Évora and Elvas, where music of Palestrina coexisted with manuscripts and prints of other Portuguese (i.e. Manuel Cardoso, Duarte Lobo and Filipe de Magalhães) and Spanish (i.e. Juan Navarro, Juan Esquivel and Tomás Luis de Victoria) masters. Following the network of these musical centres with the Spanish counterparts – notably the Capilla Real in Madrid – this study will focus on the works of Palestrina extant in Évora, Elvas and Vila Viçosa and the links to a possible circulation network based in Madrid in the first half of the eighteenth century.